2011
DOI: 10.3732/ajb.1100259
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and population genetic analyses of diploid Leucaena (Leguminosae; Mimosoideae) reveal cryptic species diversity and patterns of divergent allopatric speciation

Abstract: Findings from this study highlight the importance and utility of multilocus data in the recovery of complex evolutionary histories. The results are consistent with allopatric divergence representing the predominant mode of speciation among diploid Leucaena. These findings contrast with the potential hybrid origin of several tetraploid species and highlight the importance of human translocation of seed to the origin of these tetraploids. The recognition of one previously unrecognized species (L. cruziana) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 72 publications
(130 reference statements)
1
55
1
Order By: Relevance
“…Olmstead, ), predominance of allopatry and allopatric speciation (e.g. Govindarajulu et al ., ), pre‐Pleistocene divergence time estimates for species and clade ages and well‐supported monophyly of individual species in densely sampled gene trees. Taken together, this evidence points to a scenario of dispersal limitation across the highly fragmented, disjunct distribution of SDTFs, in‐situ diversification of pairs or small clades of species in specific SDTF nuclei and long persistence and relative stasis of stable populations of SDTF species and lineages over the past two to ten or more million years (Lavin et al ., ; Lavin ; Pennington et al., , b, , ).…”
Section: Geotemporal Trajectories Of Plant Evolution and Diversificatmentioning
confidence: 76%
See 2 more Smart Citations
“…Olmstead, ), predominance of allopatry and allopatric speciation (e.g. Govindarajulu et al ., ), pre‐Pleistocene divergence time estimates for species and clade ages and well‐supported monophyly of individual species in densely sampled gene trees. Taken together, this evidence points to a scenario of dispersal limitation across the highly fragmented, disjunct distribution of SDTFs, in‐situ diversification of pairs or small clades of species in specific SDTF nuclei and long persistence and relative stasis of stable populations of SDTF species and lineages over the past two to ten or more million years (Lavin et al ., ; Lavin ; Pennington et al., , b, , ).…”
Section: Geotemporal Trajectories Of Plant Evolution and Diversificatmentioning
confidence: 76%
“…Despite a history of neglect compared to the more charismatic and widely publicized lowland tropical rain forests, research on seasonally dry tropical forests has blossomed in the last decade, revealing not only the biological importance of these forests in terms of their highly endemic floras, but also important insights into the biogeography of this biome and the processes and factors that have apparently shaped the historical assembly of SDTF species diversity (Linares‐Palomino et al ., ; Prado, ; Lavin et al ., ; Pennington et al ., , , b, , ; Lavin, ; Särkinen et al ., , ). A growing number of detailed and well‐sampled phylogenetic analyses of SDTF lineages show high levels of dry forest niche conservatism (Pennington et al ., ; Govindarajulu et al ., ), high geographical phylogenetic structure (e.g. Olmstead, ), predominance of allopatry and allopatric speciation (e.g.…”
Section: Geotemporal Trajectories Of Plant Evolution and Diversificatmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of phylogeographical studies carried out in recent years have revealed that widespread species are often subdivided into genetically distinct forms that lack morphological differences (e.g., Forsdyke 2013;Johnson et al 2013;Govindarajulu et al 2011;Pillon et al 2009;Carstens and Satler 2013;Paupério et al 2012). The discovery and characterization of these forms contribute to the understanding of speciation (Sites and Marshall 2003).…”
Section: Introductionmentioning
confidence: 98%
“…The morphological characters might be overlapping between these species and it might not be possible to distinguish them. Within the genus Leucaena (Leguminosae; Mimosoideae) cryptic diversity was found among allopatric populations (Govindarajulu et al, ). Cryptic speciation is observed frequently in mosses and liverworts which occur in a wide geographical area (McDaniel & Shaw, 2003; Yu et al, ).…”
Section: Discussionmentioning
confidence: 99%